Diagnostic Imaging of Canine Hepatobiliary Affections: A Review - Vijay Kumar; Adarsh Kumar; A. C. Varshney; S. P. Tyagi; M. S. Kanwar; S. K. Sharma (Veterinary Medicine International)
Hepatic disease is often treatable and has a predictable prognosis when a definitive diagnosis is made. The aim of clinicopathological evaluation of hepatobiliary affections is to identify and characterize hepatic damage and dysfunction, identify possible primary causes of secondary liver disease, differentiate causes of icterus, evaluate potential anaesthetic risks, assess prognosis and response to xenobiotics, and monitor response to therapy. This paper describes the different diagnostic methods and imaging techniques employed in diagnosis of hepatobiliary affections in dogs. Besides reviewing the significant clinical manifestations and imaging structural abnormalities in diagnostic approach to different hepatic affections, it also depicts radiographic, ultrasonographic, and wherever applicable, the laparoscopic characterization of different hepatic affections and target lesions encountered in clinical cases presented in the Teaching Veterinary Clinical Complex, COVAS, Palampur in the year 2007-2008.